Analysis of Microcirculation Changes in the Macular Area and Para-Optic Disk Region After Implantable Collamer Lens Implantation in Patients With High Myopia - Xu, Yingnan; Yang, Weihua; Long, Tan; Shang, Weihong; Xu, Xiangzhong; Wang, Jinfan; Yao, Jin; Li, Keran (Frontiers in Neuroscience, 2022)
Myopia has become an important public health problem to be solved urgently. This prospective cross-sectional case series aimed to observe changes in the macular retinal thickness, RNFL thickness of para-optic disc region, and blood flow density after posterior ICL implantation in patients with high myopia using OCTA. A total of 67 eyes of 67 patients with high myopia, who underwent ICL implantation at the Affiliated Eye Hospital of Nanjing Medical University from January 2020 and December 2020, were included. The SE of the operative eyes was > -6.00D. The changes in vision, IOP, SE, and vault were observed pre-operatively, and follow-up were performed 1 week, 1 month, and 3 months. OCTA was used to observe the changes in the CRT, retinal thickness of paracentral fovea, FAZ, superficial and deep retinal blood flow density in the macular area, RNFL thickness of para-optic disc region, and blood flow density before and after ICL implantation. The UDVA and best CDVA of the patients post-operation were significantly improved (P <0.001). The IOP increased in comparison with other time points at 1 week post-operation (P <0.05). There was no significant changes in CRT post-operation. The retinal thickness in the upper, lower, nasal, and temporal quadrants of the paracentral fovea increased significantly at 1 month and 3 months post-operation (P <0.05). The FAZ area at all postoperative time points were decreased (P <0.001). At 3 months post-operation, the blood flow density of the superficial and deep retinal layers in the upper, lower, and nasal macular area were significantly reduced (P <0.05). At 1 month post-operation, the RNFL thickness in the temporal para-optic disc region and blood flow density were significantly reduced (P = 0.001 and P <0.05, respectively). ICL implantation for highly myopic eyes led to an increase of the retinal thickness in the upper, lower, nasal, and temporal regions of the paracentral fovea; reduction of RNFL thickness in the temporal area of para-optic disc ; decrease in FAZ area; and decrease in the blood flow density of some deep and superficial retinal layers as well as that of the temporal para-optic disc region.